A new freshwater stygobiotic calanoid (Copepoda: Speodiaptominae) from Yunnan, China - Shu, Shusen; Brancelj, Anton; Chen, Feizhou; Yang, Junxing; Chen, Xiaoyong (Zootaxa, 2017)
Karstodiaptomus sheni n. gen., n. sp. is a new stygobiotic species of Calanoida (Crustacea: Copepoda), described from a cave in Yunnan Province, China. It is the first record of stygobiotic calanoids from China and the fourth species from Asia. To accommodate the new species, a new genus, Karstodiaptomus n. gen., was erected. The new species is distinguished from other representatives in the subfamily Speodiaptominae Borutzky, 1962 by the number of segments in the swimming legs P1–P4 (Exp + Enp) as: 2+2, 2+2, 2+2, 3+2, the armature of the antennule, maxilla, maxilliped, and the structure of the fifth leg. The position of the new species in the subfamily Speodiaptominae is discussed, and a brief note on its ecology is added.